2021
DOI: 10.7717/peerj.11835
|View full text |Cite
|
Sign up to set email alerts
|

Using in-situ environmental DNA sampling to detect the invasive New Zealand Mud Snail (Potamopyrgus antipodarum) in freshwaters

Abstract: Environmental DNA (eDNA) detection of aquatic invasive species is currently at the forefront of aquatic conservation efforts because the methodology provides a cost effective and sensitive means to detect animals at low densities. Developments in eDNA technologies have improved detection probabilities for rare, indicator, and invasive species over the past decade. However, standard lab analysis can take days or weeks before results are available and is prohibitive when rapid management decisions are required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Additional detections with eDNA sampling on this landscape were consistent with eDNA transport from a nearby, hydrologically connected site with known historical species occurrence. Further, the performance of Pyrgulopsis eDNA sampling here is consistent with the literature on morphologically similar invasive hydrobiid New Zealand Mudsnails ( Potamopyrgus antipodarum ) (Goldberg et al., 2013; Ponce et al., 2021; Woodell et al., 2021). Multiple studies have found that eDNA sampling for P. antipodarum can be effective, even for low density population detection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additional detections with eDNA sampling on this landscape were consistent with eDNA transport from a nearby, hydrologically connected site with known historical species occurrence. Further, the performance of Pyrgulopsis eDNA sampling here is consistent with the literature on morphologically similar invasive hydrobiid New Zealand Mudsnails ( Potamopyrgus antipodarum ) (Goldberg et al., 2013; Ponce et al., 2021; Woodell et al., 2021). Multiple studies have found that eDNA sampling for P. antipodarum can be effective, even for low density population detection.…”
Section: Discussionsupporting
confidence: 87%
“…For example,Goldberg et al (2013), using a taxon-specific qPCR assay, were successful in detection of P. antipodarum at densities as low as one individual per 1.5 L of water. In natural systems,Ponce et al (2021) reported concordance in eDNA sampling and conventional kick-net sampling for P. antipodarum across six streams in Washington (USA) andWoodell et al (2021) reported detection of a new invasion with eDNA sampling in Pennsylvania (USA), which was later confirmed with conventional sampling.…”
mentioning
confidence: 80%
“…Specifically, the estimation of species abundance is a significant challenge in eDNA analysis (Harper et al, 2019; Roussel et al, 2015). Although the eDNA concentration shows a positive correlation with target species abundance for multiple taxa (Pilliod et al, 2013; Ponce et al, 2021; Takahara et al, 2012; Uthicke et al, 2018; Wu et al, 2018), in natural environments, these relationships are weakened compared with those in controlled laboratory conditions (Yates et al, 2019). Numerous environmental factors complicate the diffusion, retention, and degradation of eDNA in natural environments (e.g., temperature fluctuation, water chemistry, and hydrogeographic conditions), which renders eDNA quantification and its relationship with species abundance in the field unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, biomonitoring of marine NIS can be daunting and time‐consuming, especially in large expanses of coastal marine habitats. Therefore, recent efforts have been made to strengthen marine biosecurity programs by including more sensitive and effective methods, such as molecular detection, to enhance marine NIS surveillance (Acosta et al, 2020; Eble et al, 2020; Ponce et al, 2021).…”
Section: Introductionmentioning
confidence: 99%